THE SPATIAL KALEIDOSCOPE IN THE HISTORICAL NOVEL CABOCLA (1949) - Peliceri da Silva, John David [UNESP] (Univ Estadual Mato Grosso Sul, 2020)
The space kaleidoscope is still an enigma to analyze the characteristics of the beautiful aesthetic. The historical novel Cabocla (1949), by Ribeiro Couto, brings the characteristics of the beautiful through the space of the narrative. In this article, we will analyze how the protagonist Jeronimo looks at the kaleidoscope of beauty that is found in immanent, idyllic and romantic spaces, with the purpose of understanding existence. We are based on the studies of the beauty of Kant (2005), Weiskel (1994) and Schopenhauer (2003), as well as on the concept of image description by Careri (2014) that highlights the presence of the symbolic reference. Using a symbolic language, we will explain how the ineffable beauty is present in the minimal phenomena that enchant the characters' bucolic life, from the chronotopic view. In Jeronimo's view, we realize that the recurrences of the beautiful are discursive images, organized by adjectives, natural landscapes and personification of beings.
Keywords: Jeronimo; Zuca; cabocla; space; beautiful